Students' difficulties in writing an argumentative essay: a qualitative study of EFL learners in a writing class - Siti Maria Ulfa; Moh. Arief Wahyudi (Universitas PGRI Madiun, 2023)
This study investigates the students' difficulties in producing argumentative text in a writing classroom. This qualitative study seeks to understand and interpret the meaning that individuals and groups assign to their experiences, interactions, and perceptions. The interview results were also analyzed to conclude and answer the research problem. It was found that there are several difficulties that students may need help with writing argumentative essays. One of the most significant difficulties students face in writing is requiring more time. Another one is dealing with language difficulty. Writing in a foreign language can be a significant barrier.